Synthesis, Antimicrobial, and Anticancer Activities of Novel Nitrofuran Derivatives - Malik Suliman Mohamed; Khaled M. Elamin; Rawaf Alenazy; Eyman Mohamed Eltayib; Mona Timan Idriss; Noura A. A. Alhudaib; Tilal Elsaman; Magdi Awadalla Mohamed (Journal of Chemistry)
Keeping in view the varying therapeutic attributes of 5-nitrofuran and isatin derivatives, novel 5-nitrofuran‒isatin molecular hybrids (2, 5–7) were synthesized by standard protocols, characterized by various spectroscopic techniques, and eventually evaluated against a group of pathogenic bacteria and fungi. Greater potency against Methicillin-resistant Staphylococcus aureus (MRSA) was exhibited by hybrids 5 and 6 with minimum inhibitory concentration values of 8 and 1 μg/mL, respectively. Cytotoxicity against both human embryonic kidney cells (HEK-293) and human red blood cells (RBCs) was investigated for the hybrids in hand. All hybrids appeared to have good safety; all of them were devoid of cytotoxicity, and none displayed hemolytic activity at the highest test concentration (CC50 and HI10 > 32 μg/mL). To support the postulation that these hybrids would be analogous to drugs containing the 5-nitrofurn ring system, molecular docking was carried out to streamline the binding affinity of the investigated hybrids towards the E. coli nitroreductase (NTR). Compared to the standard drug nitrofurazone, hybrid 6 demonstrated a higher affinity and better binding interactions with the NTR binding pocket. Therefore, it could be concluded that 6 displays its antibacterial action through a mechanism similar to that of nitrofurazone. Nonetheless, further wet investigations are to be conducted to confirm this finding. Encouraged by the well-established anticancer activity of isatin derivatives, 2, 5–7 were assessed for their potential antitumor activity, and they well demonstrated potent inhibitory activity against the human colon cancer cell line HCT 116 (IC50 = 1.62–8.8 μM) with isatin hybrid 3 being the best (IC50 = 1.62 μM). Thus, it is herein reported that these 5-nitrofuran‒isatin molecular hybrids could represent an ideal starting point for future studies to develop potent antimicrobial agents.